Approaching Ijmāʿ: Sociological, Theological and Legal Dimensions of Consensus in Islam - Mohamed Mosaad Abdelaziz Mohamed (Universitas Islam Negeri Mataram, 2020)
Presenting the emergence and development of ijmāʿ, this paper aims to epistemologically critique the articulation of ijmāʿ in modern Western scholarship on Islam. The article argues that to understand ijmāʿ, we need to explore its social context, theological foundations, and practical consequences. A tolerance of the difficulty in identifying truth, an understanding of the law as being built on uncertainty, and employing jamʿ, as an assemblage are essential dynamics in the formation of the law and Muslim societies. The corpus of classical literature on ijmāʿ is expectedly contradictory, and full of gaps. Rather than seeing this as problematic, the article recognizes it as normative. Against the argument that ijmāʿ was the “foundation of foundations,” or that it was a well-defined concept that gained political power against adversaries, the article argues that in practice ijmāʿ remained marginal, and confined to the minimum necessary for each individual to be a member in the Muslim community.